2022
DOI: 10.3390/ma15155359
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Benefit Assessment of Blended Cement with Modified Granulated Copper Slag

Abstract: This study aimed to investigate the environmental impact of modified granulated copper slag (MGCS) utilization in blended cement production at a representative cement plant in China. Sensitivity analysis was performed on the substance inputs, and the life cycle impact assessment (LCIA) model was applied. A detailed comparative analysis was conducted of the environmental impact of cement production in other studies, and ordinary Portland cement production at the same cement plant. Results showed that calcinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Each cycle was four hours apart and conducted over a temperature range of 4°C to -18°C, repeating up to 300 times. The study concluded after 300 cycles, and consequently, the stability coefficient of the cycles was determined [47][48][49] .…”
Section: Assessing Concrete Stability Against Freezingmentioning
confidence: 99%
“…Each cycle was four hours apart and conducted over a temperature range of 4°C to -18°C, repeating up to 300 times. The study concluded after 300 cycles, and consequently, the stability coefficient of the cycles was determined [47][48][49] .…”
Section: Assessing Concrete Stability Against Freezingmentioning
confidence: 99%
“…In CBMs, CS can be used as supplementary cementitious materials (SCMs) to reduce cement consumption, thus saving a lot of energy consumption when producing cement [ 8 , 9 ]. When CS after grinding as a kind of SCMs is added to CBMs, it delays the setting time of CBMs [ 10 , 11 , 12 , 13 ], it does not affect the working properties of CBMs [ 14 , 15 ], it improves the mechanical properties of CBMs [ 10 , 16 , 17 ], and it enhances the durability of CBMs [ 15 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%